Local charge trapping in conjugated polymers resolved by scanning Kelvin probe microscopy - Hallam, Toby; Lee, MiJung; Zhao, Ni; Nandhakumar, Iris; Kemerink, Martijn; Heeney, Martin; McCulloch, Iain; Sirringhaus, Henning (Physical review letters, 2009)
The microstructure of conjugated polymers is heterogeneous on the length scale of individual polymer chains, but little is known about how this affects their electronic properties. Here we use scanning Kelvin probe microscopy with resolution-enhancing carbon nanotube tips to study charge transport on a 100 nm scale in a chain-extended, semicrystalline conjugated polymer. We show that the disordered grain boundaries between crystalline domains constitute preferential charge trapping sites and lead to variations on a 100 nm scale of the carrier concentration under accumulation conditions.
Gesehen am 16.12.2019